Rapid Detection and Quantification of Novel Psychoactive Substances (NPS) Using Raman Spectroscopy and Surface-Enhanced Raman Scattering - Muhamadali, Howbeer; Watt, Alexandra; Xu, Yun; Chisanga, Malama; Subaihi, Abdu; Jones, Carys; Ellis, David I.; Sutcliffe, Oliver B.; Goodacre, Royston (Frontiers in Chemistry, 2019)
With more than a million seizures of illegal drugs reported annually across Europe, the variety of psychoactive compounds available is vast and ever-growing. The multitude of risks associated with these compounds are well known and can be life threatening. Hence the need for the development of new analytical techniques and approaches that allow for the rapid, sensitive and specific quantitative detection and discrimination of such illicit materials, ultimately with portability for field testing, is of paramount importance. The aim of this study was to demonstrate the application of Raman spectroscopy and surface-enhanced Raman scattering (SERS) combined with chemometrics approaches, as rapid and portable techniques for the quantitative detection and discrimination of a wide range of novel psychoactive substances (methcathinone and aminoindane derivatives), both in powder form and in solution. The Raman spectra of the psychoactive compounds provided clear separation and classification of the compounds based on their core chemical structures; viz. methcathinones, aminoindanes, diphenidines and synthetic cannabinoids. The SERS results also displayed similar clustering patterns, with improved limits of detections down to ~2 mM (0.41 g L-1). As mephedrone is currently very popular for recreation use we performed multiplexed quantitative detection of mephedrone (4 methyl methcathinone), and its two major metabolites (nor-mephedrone and 4 methylephedrine), as tertiary mixtures in water and healthy human urine. These findings readily illustrate the potential application of SERS for simultaneous detection of multiple NPS as mixtures without the need for lengthy prior chromatographic separation or enrichment methods.